2022
DOI: 10.1155/2022/8115173
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Acylcarnitine and Peripheral Neuropathy in Type 2 Diabetes Mellitus

Abstract: Objective. In patients with type 2 diabetes mellitus (T2DM), it is unknown whether acylcarnitine changes in the patient’s plasma as diabetic peripheral neuropathy (DPN) occurs. The purpose of the present study was to investigate the correlation between acylcarnitines and DPN in Chinese patients with T2DM. Methods. A total of 508 patients admitted to the First Affiliated Hospital of Jinzhou Medical University were included in this study, and all of whom were hospitalized for T2DM from January 2018 to December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…DPN is one of the most common chronic complications of diabetes [ 15 , 16 ]. It is characterized by insidiousness and difficulty to detect.…”
Section: Discussionmentioning
confidence: 99%
“…DPN is one of the most common chronic complications of diabetes [ 15 , 16 ]. It is characterized by insidiousness and difficulty to detect.…”
Section: Discussionmentioning
confidence: 99%
“…A 6-year prospective study of 2103 community-dwelling individuals aged 50-70 years in Beijing and Shanghai, China, with type 2 diabetes as the observed outcome found higher plasma concentrations of short-, medium-, and long-chain acylcarnitines at baseline, but only long-chain acylcarnitines were significantly associated with the risk of type 2 diabetes [34]. A previous study found that elevated levels of short-and medium-chain acylcarnitines in blood were associated with the risk of developing cardiovascular disease in T2DM [35]. A study on diabetic peripheral neuropathy (DPN) claimed that C4DC and C24 concentrations in non-DPN plasma were significantly higher than in DPN patients and that factors containing C2, C3, C4, and C5 short-chain acylcarnitines were positively associated with the risk of DPN in T2DM [36].…”
Section: Discussionmentioning
confidence: 81%
“…Acylcarnitines are involved in fatty acid β-oxidation and the branched-chain amino acid metabolism, including valine, leucine, and isoleucine, associated with the progression of AIDs ( 31 , 32 ). Observational research has established a positive correlation between blood acylcarnitine levels and peripheral neuropathy in type 2 diabetes patients ( 33 ). It is also suggested that IVC may accelerate the progression of rheumatoid arthritis ( 4 ).…”
Section: Discussionmentioning
confidence: 99%